Peer Relationships and College Students’ Cooperative Tendencies: Roles of Interpersonal Trust and Social Value Orientation - Wang, Gaofeng; Hu, Weiwei (Frontiers in Psychology, 2021)
The current study investigated the relationship between peer relationships and cooperative tendencies in college students, and explored the mediating role of interpersonal trust and the moderating role of social value orientation in that relationship. A questionnaire was distributed to 406 college students, and the results showed that: (1) peer relationships significantly positively predicted cooperative tendencies; (2) interpersonal trust partially mediated the relationship between peer relationships and cooperative tendencies; and (3) social value orientation moderated the relationship between peer relationships and cooperative tendencies. In particular, prosocial college students were more susceptible to peer relationships than pro-self college students. The findings of the current study indicated that college students with good peer relationships and prosocial value orientation are more likely to show the willingness to cooperate.